Literature Review: Edible-Film Dipped Apple Cider as an Instant Drink Innovation - Arisya Falah Silmi (Jurnal Agroindustri Pangan, 2024)
Instant drinks are a type of practical, ready-to-drink beverage product that consumers can purchase and enjoy at any time. One product that is often found is fruit juice soft drink products. Apples are one of the horticultural products that are most in demand and consumed by the public. Apart from being bought and sold in whole form, apples are also widely processed into various food or drink products, one of which is instant drink powder. Instant powdered drinks also have various advantages, including being easy to serve in a short time, being in the form of dry fine granules with a low water content so that the product has a long shelf life, and can be made using an easy and cheap method. The method used in this research is a literature study, in the form of analysis of scientific articles from various journals which discuss the composition of ingredients, how to make apple juice, how to make edible film packaging, and the benefits obtained from this instant drink made from apples. The innovation in processed products made from apples presented in this literature review is the idea of an instant drink of dipped apple juice packaged in edible film. This innovation is a combination of creating practicality, but also maintaining environmental friendliness. Apart from that, the innovation of dip packaging which usually uses cloth tea bags by changing it to edible film packaging can also reduce the waste that is usually produced from instant dipped beverage products because of the nature of edible film packaging which is water soluble and can be consumed.